Safety of Lipid-Lowering Therapy with Statins according to a Regional Pharmacovigilance Centre - E. O. Kochkina; N. V. Verlan (Безопасность и риск фармакотерапии)
Scientific relevance. Since statins are widely used to prevent cardiovascular diseases, the control of statin-related complications is essential from both medical and social perspectives.Aim. The study aimed to analyse unsolicited reports on adverse drug reactions (ADRs) to control the safety of statin therapy.Materials and methods. The study analysed information on ADRs observed during statin treatment from the reporting forms submitted by medical organisations in Irkutsk to the database of the Regional Centre for Drug Safety Monitoring of the Irkutsk Region in 2011–2022. The causal relationship between ADRs and statin therapy was assessed using the Naranjo scale.Results. The database contained 1068 ADR reporting forms; 12 (1.1%) were spontaneous reports of statin-related complications, including 4 cases (33.4%) of myalgia, 7 cases (58.3%) of myalgia with moderately elevated transaminase levels (3–5 times the upper limit of normal), and 1 case of rhabdomyolysis that required statin discontinuation. In all cases, a reduction in the statin dose resulted in a regression in the clinical symptoms of ADRs. Most ADRs were observed in women with comorbidities (diabetes mellitus, obesity, and hypothyroidism), but the small sample size prevented the authors from testing the identified differences for statistical significance.Conclusions. According to the study results, statins have a reliable safety profile. Adequate and patient-specific selection of statin doses and ADR prevention are important responsibilities of clinical practitioners.